S34 Supporting self-management of indoor asthma triggers and allergens in children & teens with severe asthma: what do families value and what further information do they need?. (11th November 2022) - Lewis, G; Milnes, L; Adams, A; Schwarze, J; Duff, A
Abstract : Introduction: Families of children and young people (CYP) with asthma are tasked with asthma trigger and indoor allergen avoidance as part of supported self-management. However, multiple triggers exist, and CYP are often poly-sensitised to allergens, complicating identification of asthma triggers and decisions regarding remediation. A scoping review identified very limited evidence regarding determinants of family uptake of trigger and allergen remediations. Aims: To understand the determinants of trigger and allergen avoidance from perspectives of families of CYPs with severe asthma and allergic sensitisation to indoor environmental allergens, to provide insight for future interventions to increase avoidance uptake. Methods: In-depth qualitative interviews with CYP aged 11–16-years, with severe asthma and allergic sensitisation to pets and/or house dust mites, and CYPs' parents were conducted. Grounded theory methodology guided study design and analyses. Results: 21 individuals (11 mothers and 10 CYP) participated. Multiple factors affect families' decisions about trigger and allergen avoidance, including perceived asthma severity, observable response to exposures, and the acceptability of remediation methods. Families value discussion of individualised needs and barriers to avoidance uptake with health professionals. Findings suggest families with sensitised children will employ allergen remediations in response to repeated exacerbations and hospitalisations, but many do not employ methods with the greatest evidence base. Moreover, avoidance uptake was often many years after initial advice was given following allergen testing. Families also struggled to understand the mechanisms linking allergen exposure and asthma control. Conclusions: Families may benefit from educational interventions to enhance understanding of the mechanisms linking allergen and trigger exposures with asthma control. Interventions could aim to explain which allergen reduction methods currently show effectiveness for CYP with asthma. Additionally, interventions addressing the delayed uptake of avoidance could aid self-management. Please refer to page A208 for declarations of interest related to this abstract.